2018
DOI: 10.1002/marc.201700835
|View full text |Cite
|
Sign up to set email alerts
|

Macroscopic Adhesion of Thermoreversible ABC Triblock Copolymer‐Based Hydrogels Via Boronic Acid–Sugar Complexation

Abstract: Two complementary thermoreversible ABC triblock copolymers containing either phenylboronic acids with low pK values or galactosyl groups in the hydrophilic B blocks are synthesized by sequential reversible addition-fragmentation chain transfer polymerization and subsequent modification of the functional groups. Both ABC triblock copolymers undergo reversible sol-to-gel transitions upon temperature change and form physically cross-linked hydrogels under physiological conditions. Furthermore, the spontaneous adh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Tamate et al. also reported assembling thermoreversible hydrogels constructed using an ABC‐type triblock copolymer containing PBA moiety in the B block and the same polymer containing galactosyl moiety in the B block . Two kinds of thermoreversible hydrogels adhered to each other by the boronate‐galactose interaction under physiological conditions.…”
Section: Meso‐ and Macroscopic Hybrid Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tamate et al. also reported assembling thermoreversible hydrogels constructed using an ABC‐type triblock copolymer containing PBA moiety in the B block and the same polymer containing galactosyl moiety in the B block . Two kinds of thermoreversible hydrogels adhered to each other by the boronate‐galactose interaction under physiological conditions.…”
Section: Meso‐ and Macroscopic Hybrid Materialsmentioning
confidence: 99%
“…Winblade et al also reported a strategy to block adhesion of cells to extracellular matrices using the same polymers. [33] A tissue culture polystyrene dish was coated with the copolymer, preventing adhesion of rabbit lens epithelial cells to the surface. The polymer also enhanced surgical lysis of peritoneal adhesions in rats.…”
Section: Materials Interacting With Cellsmentioning
confidence: 99%
“…[1][2][3][4][5][6] In the past few decades, various gel functions, including stimuli response, self-oscillation, self-healing, high mechanical strength, and biomolecular recognition, have been developed. [7][8][9][10][11][12][13] Moreover, researchers have attempted strategic control of the gel structure, [14][15][16][17][18] because the molecular design of polymer networks plays a significant role in the development of various gel functionalities. www.advancedsciencenews.com www.mcp-journal.de…”
Section: Introductionmentioning
confidence: 99%
“…In this review, we specially focused on smart materials which respond to thermal stimulus. [14][15][16][17][18] Thermally reversible materials fit into two categories: ones based on reversible weak interactions and those based on reversible covalent bonds. [19] Thermoreversible systems based on weak interactions mainly exist in materials that are able to create and break polar bonds or hydrogen bonds according to the surrounding temperature; the latter interactions entail for instance the formation of reversible chitosan/pectine hydrogels [20] or the formation of smart silica-rubber nanocomposites.…”
Section: Introductionmentioning
confidence: 99%